Evaluating maternal death surveillance and response system in Sunyani Municipality of Bono region in Ghana from 2017-2021 - Amara S. Ngegbai; George Khumalo Kuma; Charles L. Noora; Ernest Tei Maya; Chris Guure (BMC Health Services Research)
Abstract Introduction Maternal death rates in Ghana have decreased overall but remain high in rural areas. The Maternal Death Surveillance and Response System (MDSR) aims to eliminate preventable maternal deaths effectively. However, its effectiveness is less pronounced at district and subdistrict levels than at national and regional levels. Despite the requirement for periodic evaluation, there is a lack of evidence supporting these assessments. This study focuses on evaluating the MDSR in Sunyani Municipal. Methods The evaluation was conducted using a cross-sectional design, using both qualitative and quantitative approaches. Data from the District Health Information Management Systems (DHIMS) and the maternal death line list from January 2017 to December 2021 on maternal deaths were reviewed. Stakeholders, including health professionals, were interviewed. The means, proportions, and other statistical measures were calculated using Epi Info Version 7. Qualitative data underwent content analysis, and the results were visually presented in tables and flowcharts to illustrate the flow of surveillance information. Results Most respondents were female, constituting 51.4% (19/37), with midwives comprising the largest group at 32.4% (12/37). Approximately 75.7% (28/37) were able to explain how the surveillance data has been used for public health action. The notification and reporting process was clear to 85% (17/20) of respondents. Although 94.6% (35/37) expressed willingness to notify and participate in audits at facility and community levels, the audits remained facility-based. All facilities consistently reported maternal deaths, but data storage equipment was lacking. Approximately 80% (20/25) of forms were reported within 24 h, and 88% (22/25) were investigated within seven days. Only 68% (17/25) of forms were filled out correctly, with no municipal and facility-level line list. All reported deaths came from healthcare facilities, with no community-reported maternal deaths. Conclusions The MDSR system in Sunyani Municipal demonstrates high awareness and willingness to participate among healthcare providers but faces challenges in data accuracy and community engagement. Death audits remain facility-based, and the lack of community-reported maternal deaths and municipal-level line lists indicates gaps in comprehensive reporting and data management. To improve the system, it is recommended that community case searches be enhanced for better reporting and to address data management issues by ensuring proper data quality assessment.